2001
DOI: 10.2169/internalmedicine.40.1037
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Syndrome and Adult Still's Disease Associated with Meningoencephalitis and Unconsciousness.

Abstract: Wedescribe a 19-year-old womanwith hemophagocytic syndrome and adult Still's disease who showed rare features of central neurological involvement, including cerebellar symptoms and the suddenonset of unconsciousnesswith pleocytosis in the cerebrospinal fluid during the early course of the illness. As this patient's serum showed a high level of interferon-y and soluble interleukin 2 receptor, this might play a pathologic role in the development of central nervous system symptoms. Intensive treatment consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Plasma exchange has been reported to be effective for AOSD-associated MAS (35)(36)(37). Ito et al demonstrated the prompt improvement of hypercytokinemia due to IL-6 and IL-18 using plasma exchange and a high-dose corticosteroid (37).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma exchange has been reported to be effective for AOSD-associated MAS (35)(36)(37). Ito et al demonstrated the prompt improvement of hypercytokinemia due to IL-6 and IL-18 using plasma exchange and a high-dose corticosteroid (37).…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments for HLH accompanying connective tissue diseases, such as plasma exchange therapy (PE) and anticytokine therapies including biologics have been used mainly in adult-onset Still's disease (AOSD) or systemic juvenile idiopathic arthritis (sJIA) [17][18][19] but not in DM cases complicated by HLH. Nishida et al [18] reported the case of a patient with AOSD complicated by hemophagocytic syndrome who lost consciousness due to meningoencephalitis and was successfully treated with PE. They stated that CNS symptoms such as coma and confusion were induced by increased blood cytokines, including IFN-c and sIL-2R, and that PE was effective because it rapidly decreased the circulating cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe AOSD can result in a macrophage-activating condition, resulting in HPS [5,6]. Confirming a diagnosis of malignant lymphoma, computed tomographic (CT) scans and biopsy of the swollen lymph node play an important role because malignant lymphoma usually represents lymphadenopathy [7].…”
Section: Introductionmentioning
confidence: 99%